Pengaruh Leader Member Exchange dan Work Family Conflict Terhadap Kinerja Pegawai dengan Komitmen Organisasi Sebagai Variabel Mediasi - Br. Siburian, Mery Indah (Graha Mitra Edukasi, 2023)
This study aims to determine the leader member exchange and work family conflict on employee performance with organizational commitment as an intervening variable at the office of the Sumatran II River Region Hall. Path analysis research design is used as an analytical tool used as an analytical tool to determine the direction of the variables studied and justify how significant the influence of the independent variable with the independent with the dependent is either directly or indirectly through the mediating variable. In this study, descriptive analytic method was used with a cross sectional approach. In this study, the entire population was sampled, namely 100 employees at the Sumatra II river area hall. The results of this study indicate that the leader member exchange variable has a significant effect on organizational commitment. Work family conflict has no significant effect on organizational commitment. Leader member exchange has a significant effect on employee performance. Work family conflict has a significant effect on employee performance. Organizational commitment has a significant effect on employee performance. Organizational commitment cannot mediate the influence of leader member exchange on employee performance. Organizational commitment can mediate the effect of work family conflict on employee performance.